2018
DOI: 10.1177/2278533718800625
|View full text |Cite
|
Sign up to set email alerts
|

Personal and In-store Factors Influencing Impulse Buying Behavior among Generation Y Consumers of Small Cities

Abstract: For decades, impulse buying is considered to be one of the significant factors to increase sales volume in the retail sector. Past studies have investigated the impulsive buying behavior of generation Y consumers in retail settings of somewhat medium-and large-sized cities. Therefore, how certain situational or in-store factors can propagate impulse buying in the retail settings of small cities has been widely ignored. This article explores the influence of situational variables categorized as personal factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 42 publications
5
50
0
8
Order By: Relevance
“…İlgili faktörlere göre plansız satın alma davranışı araştırmacılar tarafından farklı şekilde sınıflandırılmıştır. Bu çalışmada ise plansız satın alma davranışı üzerinde etkili olan faktörler; "dışsal tetikle-yiciler" (Mohan, Sivakumaran ve Sharma, 2013;Rasheed, Yaqup ve Baig, 2017;Tinne, 2011), "içsel tetikleyiciler" (Rook ve Gardner, 1993;Beatty ve Ferrell, 1998), "tüketicilere ilişkin durumsal faktörler" (Virvilaite, Saladiene ve Bagdonaite, 2009;Husnain, Rehman, Syed ve Akhtar, 2019) ve "tüketicilerin demografik özellikleri" (Awan ve Abbas, 2015;Ekeng, Lifu ve Asinya, 2012) şeklinde sınıflandırılmıştır.…”
Section: Plansız Satın Alma Davranışıunclassified
“…İlgili faktörlere göre plansız satın alma davranışı araştırmacılar tarafından farklı şekilde sınıflandırılmıştır. Bu çalışmada ise plansız satın alma davranışı üzerinde etkili olan faktörler; "dışsal tetikle-yiciler" (Mohan, Sivakumaran ve Sharma, 2013;Rasheed, Yaqup ve Baig, 2017;Tinne, 2011), "içsel tetikleyiciler" (Rook ve Gardner, 1993;Beatty ve Ferrell, 1998), "tüketicilere ilişkin durumsal faktörler" (Virvilaite, Saladiene ve Bagdonaite, 2009;Husnain, Rehman, Syed ve Akhtar, 2019) ve "tüketicilerin demografik özellikleri" (Awan ve Abbas, 2015;Ekeng, Lifu ve Asinya, 2012) şeklinde sınıflandırılmıştır.…”
Section: Plansız Satın Alma Davranışıunclassified
“…In fact, this is normally acceptable. Beyond gender identity, the consumers' impulse buying behavior is affected by many factors such as store atmospherics, sales promotions, salespersons' behaviors, pricing strategies (Tinne, 2011;Rasheed et al, 2017;Husnain et al, 2019), consumers' moods (Rook & Gardner, 1993), demographic characteristics (Ekeng et al, 2012;Awan & Abbas, 2015) and the literature supports this.…”
Section: Conclusion and Suggestionsmentioning
confidence: 99%
“…Virvilaite et al (2009) who proposed a theoretical model of impulse buying behavior found that situational factors related to consumers such as consumer time, influence group had an effect on impulse buying behavior. Husnain et al (2019) examined the generation Y consumers' impulse buying behavior in small cities and found that time availability and family influence factors positively affect impulse buying behavior but money availability negatively.…”
Section: Impulse Buying Behaviormentioning
confidence: 99%
“…Yu and Bastin (2010) deliberated on the role of store employees in motivating and complementing customers, thus leading to impulse buying. Atulkar and Kesari (2018) and Husnain et al (2019) mentioned that friendly employees play an important role in an impulse purchase. Badgaiyan and Verma (2015) reflected on family influence on impulse buying.…”
Section: External Stimulimentioning
confidence: 99%